Bridging Tradition and Faith: Islamic Da'wah and the Evolution of Malay Marriage Customs in South Sumatra - Yusnita, Eti; Gibtiah, Gibtiah (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2024)
The acculturation of Islam in the marriage customs of the Malay community of South Sumatra reflects a harmonious combination of Islamic values and local customs. Marriage is an important event involving the married individual and the family relationship. This study aims to analyze the acculturation of Islam in the marriage customs of the Malay community of South Sumatra, especially among the Semende tribe. This study uses a qualitative approach with observation, interview, and document analysis methods. The study results show that Islamic values are integrated into the traditional procession of marriage, from pre-marriage to wedding celebrations, creating a balance between local traditions and Islamic law. For example, the marriage custom of